Criptografia Baseada em Identidade: Uma Análise Comparativa sob a Perspectiva da Internet das Coisas - Maia Neto, Antonio L.; Nogueira, Michele; Patil, Harsh Kupwade; Cunha, Ítalo; Loureiro, Antonio A. F.; Oliveira, Leonardo B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2015: Anais do XV Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2015)
Identity-Based Cryptography (IBC) employs user's identity as public key, eliminating digital certificates. IBC is promising in constrained environments as Internet of Things (IoT) due to its benefits, such as facilitating public key management. However, different aspects on IBC (e.g. the need for bilinear pairing) require attention when applied to IoT in order to meet basic security requirements on these environments. This paper presents a comparative analysis of identity-based cryptosystems considering their application in IoT. The main characteristics of IoT serve as reference for the analysis. Hence, this paper contributes giving an overview about the benefits and drawbacks of the main identity-based cryptosystems on IoT.